Languages and Cross-Cultural Exchanges in Renaissance Italy - Petrocchi, Alessandra; Brown, Joshua (Brepols, 2023)
Although much work has been done in the field of Renaissance Studies, at present there is no book which offers a comparative overview of the linguistic interaction between Renaissance Italy and the wider world. The present volume is intended to fill this void, representing the first-ever collection of essays that deal with multiple types of language contact and cross-cultural exchanges <span class=